1994
DOI: 10.1111/j.1600-0528.1994.tb01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial modeling for root caries prediction: 3‐year follow‐up results

Abstract: The study was part of a series aiming at the development of caries tests. The initial material (n = 104, age range 47-79 yr, mean 62 yr) was reduced to 96, who were observed for 3 yr. During the follow-up four subjects died, all due to myocardial infarction, and four refused to participate. Thorough oral examinations were conducted at the baseline, 1- and 3-yr registrations; coronal and root surface caries were registered separately according to WHO classification. The tests included salivary mutans streptococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 18 publications
0
47
1
Order By: Relevance
“…Both studies reported a similar 2-year incidence of 36%. Two other risk models also showed that baseline root DFS was a highly significant predictor of 3-year RC incidence [Scheinin et al, 1994], and that the baseline RCI was significantly correlated with RC incidence [Powell et al, 1991].…”
Section: Root Caries Predictionmentioning
confidence: 88%
“…Both studies reported a similar 2-year incidence of 36%. Two other risk models also showed that baseline root DFS was a highly significant predictor of 3-year RC incidence [Scheinin et al, 1994], and that the baseline RCI was significantly correlated with RC incidence [Powell et al, 1991].…”
Section: Root Caries Predictionmentioning
confidence: 88%
“…A previously developed multifactorial model for root caries prediction [Scheinin et al, 1992[Scheinin et al, , 1994 showed that the highest predictive value for root caries increment came from the combination of past root caries experience, visible plaque, and high numbers of candida and LB in stimulated whole saliva. When salivary flow rate, SM and LB counts, old age and male gender were included, our log-linear model explained 54% of the variation in the occurrence of DRS.…”
Section: Discussionmentioning
confidence: 99%
“…A predictive power of the level of bacteria from the S.m. group in the saliva as a single predictor is generally weak (Scheinin et al 1994). The positive predictive value may also be adversely affected by low caries experience (Beck 1990).…”
Section: Streptococcus Mutans Groupmentioning
confidence: 98%
“…The positive predictive value may also be adversely affected by low caries experience (Beck 1990). However, the caries predictive power increases when these tests are included in multifactorial models for caries prediction (Leverett et al 1993;Bratthall and Hänsel Petersson 2005;Tamaki et al 2009;Scheinin et al 1994). Table V provides the summated values of sensitivity, specificity and predictive values of POC tests for detection of salivary S.m.…”
Section: Streptococcus Mutans Groupmentioning
confidence: 99%